Human Factor Errors That May Occur During The Technical Maintenance Process In Air Transport - Qabulova S.R.; Tursunov Z. Sh. (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Currently, a large number of flights are being carried out in air transport. To ensure the safe operation of these flights, the technical maintenance process in aviation is considered highly responsible and high-risk. Therefore, all these activities ultimately depend on the human factor. This article provides information about human errors encountered in aviation technical maintenance and the PEAR model.